Diet and subsistence in the Anglo-Saxon Trent Valley: a stable isotope investigation of Broughton Lodge Anglo-Saxon cemetery, Nottinghamshire - Moore, Fiona E. (2017)
Stable isotope analysis was carried out on a small sample population from Broughton Lodge Anglo-Saxon cemetery, Nottinghamshire. The cemetery dates to the late 5th to the early 7th centuries AD, and is located in the Trent valley, which was the centre of the Anglo-Saxon kingdom of Mercia. The broad aim was to investigate diet, subsistence, and breastfeeding and weaning practices. Rib bone and permanent second molar and premolar dentine collagen was sampled from six individuals from the cemetery population, to investigate the adult and childhood diets of the Broughton Lodge population. Incremental dentine analysis was carried out on the permanent first molars of two of the individuals, to investigate breastfeeding and weaning practices amongst the population. The results have shown that the diet of the Broughton Lode population was very similar to that at other Anglo-Saxon sites in England, comprised primarily of terrestrial animal protein with some amounts of freshwater fish. There was no significant difference in basic protein sources noted between adult and childhood diet. The results of the incremental analyses were inconclusive. A definite breastfeeding and weaning signal could not be inferred for either individual, although several observations were made. The research has highlighted the need for further stable isotope studies in the Trent valley focussing on the Anglo-Saxon period.